Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2016
DOI: 10.24953/turkjped.2016.02.001
|View full text |Cite
|
Sign up to set email alerts
|

Serum vitamin D levels during activation and remission periods of patients with juvenile idiopathic arthritis and familial Mediterranean fever

Abstract: The aim of this study was to determine the frequency of vitamin D deficiency and/or insufficiency in children with juvenile idiopathic arthritis (JIA) and familial Mediterranean fever (FMF) and to assess the relationship between vitamin D and disease activity. Sixty four patients with JIA, thirty six patients with FMF and one hundred healthy children were enrolled in this study. Vitamin D levels were measured during activation and remission periods in the patients with JIA and during attack and attack free per… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
28
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 23 publications
(40 citation statements)
references
References 27 publications
6
28
2
Order By: Relevance
“… Illinois, USA Reed et al 1991 40°N [ 46 ] JRA n = 13 (12F) 5–18 70.0 ± 40 Vitamin D may help prevent bone loss in children with active disease. Study Design: Case-Control Istanbul, Turkey Dagdeviren- Cakir et al 2016 41°N [ 21 ] JIA Active disease: n = 64 (41) Remission: 53(35) Active disease: 9.7 ± 4.3 Remission: 9.8 ± 4.3 Active disease: 46.5 ± 23.0 Remission: 47.3 ± 27.5 Vitamin D concentrations in children with JIA were significantly lower than healthy children. Of those who were measured while in remission there was no difference in 25(OH)D concentrations.…”
Section: Results Of Scoping Review and Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“… Illinois, USA Reed et al 1991 40°N [ 46 ] JRA n = 13 (12F) 5–18 70.0 ± 40 Vitamin D may help prevent bone loss in children with active disease. Study Design: Case-Control Istanbul, Turkey Dagdeviren- Cakir et al 2016 41°N [ 21 ] JIA Active disease: n = 64 (41) Remission: 53(35) Active disease: 9.7 ± 4.3 Remission: 9.8 ± 4.3 Active disease: 46.5 ± 23.0 Remission: 47.3 ± 27.5 Vitamin D concentrations in children with JIA were significantly lower than healthy children. Of those who were measured while in remission there was no difference in 25(OH)D concentrations.…”
Section: Results Of Scoping Review and Discussionmentioning
confidence: 99%
“…Twenty-one of the 38 studies (55.3%) reported 25(OH)D status for patients with JIA [ 21 40 ], eight (21.1%) for patients with JRA [ 41 48 ] and five (13.2%) for JCA patients [ 49 – 53 ]. Additionally, there were four studies that included patients with juvenile arthritis and other rheumatic diseases [ 54 57 ].…”
Section: Results Of Scoping Review and Discussionmentioning
confidence: 99%
“…Thus, the JIA treatment should be prompt and effective. The importance of supportive measurements, such as adequate nutrition, calcium and Vitamin D supplements, should not be underestimated (7,45,46). The aim of the therapy should be multidimensional: to control the pain, to preserve the range of motion/muscle strength/muscle function, to induce disease remission, to manage systemic complications and to facilitate normal physical and psychosocial development.…”
Section: Juvenile Idiopathic Arthritis Subtypesmentioning
confidence: 99%
“…Results: We followed 31 patients (81% female) suffering from JIA with ocular manifestations. Median age at JIA onset in girls was 2.5 (1)(2)(3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14) years and in boys 8.6 (1-14.5) years, while girls had median age 4.25 (1)(2)(3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14) years at first ocular manifestation and boys 8.25 (4 -13.5) years. All patients were RF negative.…”
Section: Resultsmentioning
confidence: 99%
“…Background: Plenty of studies demonstrated the relationship between vitamin D and Juvenile idiopathic arthritis (JIA) disease activity [1,2] .Others reported no relationship between 25(OH)D and disease activity [3,4] . The main source of vitamin D is endogenous vitamin D synthesis induced by sunlight exposure.…”
mentioning
confidence: 99%